Antibacterial Activity of Some Species of Umbelliferae - TURAN AKKOYUN, H.; DOSTBIL, NURSEL (Asian Journal of Chemistry, 2010)
In this work, the antimicrobial activities of some species of Umbelliferae (Anethum graveolens L., Petroselinum crispum, Coriandrum sativum L.) have been studied. For this purpose herb extracts which were prepared in diethyl-ether were tested to bacteria strains, P. aeruginosa ATCC 25853, E. coli ATCC 11239, K. pneumoniae FML 5, M. luteus ATCC 9345, E. faecalis ATCC 29212, B. megaterium DSM 32 and S. aureus ATCC 25923 with disk diffusion method as in vitro. It is determined that herbs which were investigated show different levels of inhibitory activity to test strains, dill affects all of the bacteria, parsley and coriander have minimum antimicrobial activity.